ANTIBACTERIAL ACTIVITY OF VARIOUS LEAF EXTRACT OF CAJANUS CAJAN L. - H. PRATIMA; PRATIMA MATHAD (The Bioscan, 2011)
The active components of Cajanus cajan L. were extracted in various organic solvents such as pet ether, chloroform, methanol, ethanol and aqueous and were tested against Bacillus subtilis, staphylococcus aureus, Streptococcus pneumonia, Salmonella typhi, Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa using agar well diffusion method. All the extracts inhibited the growth of both Gram-positive and Gram-negative bacteria. However, the chloroform extract did not show any activity against Gram negative bacteria. The ethanolic extract showed the highest activity on all the Gram positive bacteria and Gram negative bacteria Klebsiella pneumonia at 100mg/mL, where as Pseudomonas aeruginosa was resistant to all the extracts except ethanol. The minimum inhibitory concentration (MIC) of the extracts was in the range of 12.5-75 mg/mL. Preliminary phytochemical analysis of Cajanus cajan L. leaves revealed the presence of phenol, tannin, lignins, glycosids, steroids, flavonoids, alkoloids and terpenoids. The results suggest that the ethanolic leaf extract of Cajanus cajan L. showed more effective antibacterial activity against both Gram-positive and Gram-negative bacteria. There is a basis for the traditional use of the plant as a local health remedy.